Răspunsuri

2014-11-05T19:23:29+02:00
A) 5 \sqrt{2} +8 \sqrt{2} -7 \sqrt{2} = 13 \sqrt{2} -7 \sqrt{2} = 6 \sqrt{2} 

b) 5-2* \sqrt{5} * \sqrt{3} + 3 = 8-2 \sqrt{8} 

e)(4 \sqrt{3} + 3 \sqrt{3} ) * \sqrt{3} = 7 \sqrt{3} *  \sqrt{3} = 7*3=21

d) a^{2} -   b^{2} =(a-b)(a+b) ---> asta e formula

Comentariul a fost şters
Comentariul a fost şters
am pus si punctul e...
Comentariul a fost şters
Comentariul a fost şters
Cel mai inteligent răspuns!
2014-11-05T20:32:10+02:00
A)2√32=2√2²√2²√2=2·2·2√2=8√2
√98=√7²√2=7√2
=5√2+8√2-7√2=13√2-7√2==6√2
b)(√5-√3)²=√5²-√5√3-√5√3+√3²=5-√15-√15+3=8-2√15=2(4-√15)
c))=(√5-√√21)(√5+√√21)=√5²+√5√√21-√5√√21+√√21²=
5+√21
d)√27=√3²√3=3√3
(4√3+3√3)·√3=7√3·√3=7·√3²=7·3=21
1 5 1